Dissociative electron attachment to coordination complexes of chromium: chromium(0) hexacarbonyl and benzene-chromium(0) tricarbonyl - Janina Kopyra; Paulina Maciejewska; Jelena Maljković (Beilstein Journal of Nanotechnology, 2017)
Here we report the results of dissociative electron attachment (DEA) to gas-phase chromium(0) hexacarbonyl (Cr(CO)6) and benzene-chromium(0) tricarbonyl ((η6-C6H6)Cr(CO)3) in the energy range of 0–12 eV. Measurements have been performed utilizing an electron-molecular crossed beam setup. It was found that DEA to Cr(CO)6 results (under the given experimental conditions) in the formation of three fragment anions, namely [Cr(CO)5]−, [Cr(CO)4]−, and [Cr(CO)3]−. The predominant reaction channel is the formation of [Cr(CO)5]− due to the loss of one CO ligand from the transient negative ion. The [Cr(CO)5]− channel is visible via two overlapping resonant structures appearing in the energy range below 1.5 eV with a dominant structure peaking at around 0 eV. The peak maxima of the fragments generated by the loss of two or three CO ligands are blue-shifted and the most intense peaks within the ion yield curves appear at 1.4 eV and 4.7 eV, respectively. (η6-C6H6)Cr(CO)3 shows a very rich fragmentation pattern with decomposition leading to the formation of seven fragment anions. Three of them are generated from the cleavage of one, two or three CO ligand(s). The energy of the peak maxima of the [(C6H6)Cr(CO)2]–, [(C6H6)Cr(CO)]–, and [(C6H6)Cr]− fragments is shifted towards higher energy with respect to the position of the respective fragments generated from Cr(CO)6. This phenomenon is most likely caused by the fact that chromium–carbonyl bonds are stronger in the heteroleptic complex (η6-C6H6)Cr(CO)3 than in homoleptic Cr(CO)6. Besides, we have observed the formation of anions due to the loss of C6H6 and one or more CO units. Finally, we found that Cr−, when stripped of all ligands, is generated through a high-energy resonance, peaking at 8 eV.